An Observational Study of OCD Patients Treated With Cognitive Behavioral Therapy During the COVID-19 Pandemic - Zaccari, Vittoria; Gragnani, Andrea; Pellegrini, Valerio; Caiazzo, Tecla; D'Arienzo, Maria Chiara; Magno, Antonella; Femia, Giuseppe; Mancini, Francesco (Frontiers in Psychiatry, 2021)
Background and objectives: While the consequences of the COVID-19 pandemic for general mental health and the increase in anxiety and depression are clear, less is known about the potential effect of the pandemic on OCD. The purpose of this study is to collect new data to monitor the symptomatic status of patients with OCD during the period of emergency due to COVID-19 and to make a comparison between two psychodiagnostic evaluations. Methods: Eleven OCD patients and their psychotherapists were recruited. All patients had a specific psychodiagnostic assessment for OCD (SCL-90; OCI-R; Y-BOCS self-report) performed between December 2019 and January 2020 (t0), and undertook cognitive behavioral therapy (CBT) and exposure and prevention of response protocol (ERP) before the lockdown. The psychodiagnostic assessment carried out at t0 was re-administered (t1) to all patients, together with a set of qualitative questions collected through an online survey. The respective therapists were asked to document the status of the therapy and the monitoring of symptoms through use of a semi-structured interview (Y-BOCS) and a qualitative interview. Non-parametric analyses were conducted. Results: Patients reported a significant decrease in OCD symptoms. Data analysis showed a decrease in the scores across t0 and at t1 on the Y-BOCS (SR) total self-report, and on OCD symptoms’ severity assessed by means of the OCI-r and SCL-90 r OC subscale, for 11 participants. Relating to the measures detected by psychotherapists, marginally significant improvements and lower scores were found in the Y-BOCS (I). An improvement in symptoms was noticed by 90.9% of the clinical sample; this was confirmed by 45.4% of the therapists, who claimed moderate progress in their patients. Conclusions: The data collected through standardized measurements at two different times, albeit relative to a small sample, assume relevance from a clinical point of view. In the literature, some studies document the worsening of OCD. However, in many studies, the type of treatment, the detection time, and the intervention period are not well specified. These results confirm the effectiveness of CBT/ERP as an elective treatment for OCD through a specific intervention procedure.